SenseWeb: Sharing and Browsing Environmental Changes in Real Time - Luo, Liqian; Kansal, Aman; Nath, Suman; Zhao, Feng (Microsoft, 2008)
In 2008, the world was hit by some of the worst natural disasters. The Cyclone Nargis killed over 140,000 people and led to 10 billion financial losses. The Great Sichuan Earthquake caused over 60,000 deaths and 20 billion of estimated property damages. How do we get prepared for natural hazards? How do we enhance our resilience to natural hazards? Part of the answer lies in innovative techniques to monitor, model, and predict environmental changes that potentially lead to natural hazards. SenseWeb addresses this need by providing a scientific investigation platform that enables global sharing of sensory streams and real-time exploration of environmental measurements. By allowing users to create heterogeneous sensors and register distributed data feeds, SenseWeb is able to federate individually deployed sensor networks into a large-scale, unified sensing system across the globe. SenseWeb provides a web-based frontend, SensorMap, for end-users to browse real-time measurements, to discover their spatial correlations, as well as to explore historic trends.
Microsoft eScience Workshop